PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP KETERAMPILAN BERKOMUNIAKSI SISWA KELAS X MAN KISARAN TAHUN AJARAN 2019/2020 - Nefi Darmayanti; Inadaya Febriani Tanjung; Ikke Nurjannah Sinaga (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2019)
This study aims to determine the effect of group guidance services on thecommunication skills of class X students at MAN Asahan in the 2019/2020 school year. This type of research used in this study is quantitative. The design used in this study is a quasi experimental design and uses a nonequivalent control group desaign model. The research sample consisted of 30 students from a population of 380 students. The data collection instrument in this study is the scale of communication skills. Data analysis techniques in this study used the t-test formula. Based on test results using tests it is known that there are significant differences in communication skills between the posttest conditions in the control group addressed by the coefficient t of 3.797 with α <0.05 and posttest in theexperimental group as indicated by the coefficient t of 28.454 with α <0.05. Judging from the average shows that the communication skills of students in the post-test conditions in the experimental group increased when compared with the post-test conditions in the control group. It can be concluded that the group guidance service has a significant influence on improving the communication skills of class X MAN Asahan in the 2019/2020 school year.Kewords: group guidance services on the communication skills